Finnish Forest and Energy Policy Model (FinFEP) : A Model Description - Lintunen, Jussi; Laturi, Jani; Uusivuori, Jussi (Luonnonvarakeskus (Luke), 2015)
Finnish Forest and Energy Policy model (FinFEP) is a partial equilibrium model of the Finnish forest and energy sectors. The processing technologies of the two sectors are based on plant-level data. The approach falls into the bottom-up modeling tradition. In addition to the processing sectors, the model consists of a detailed description of forest resources on forestry land available for wood production in Finland. The model generates harvesting behavior based on optimized management rules and the state of the forest resources. In line with the usual CGE modeling convention, we formulate the partial equilibrium of the two sectors as a mixed complementarity problem (MCP). In this report, we describe the modeling approach in detail level, and give examples of applications that the model can be used for.
Keywords: forest sector; energy sector; modeling; age-structured forest; partial equilibrium; dnamic optimization; bottom-up approach; mixed complementarity problem; forestry sector; age structure; forests